Form-finding using nonlinear analysis method of tensioned fabric structure in the form of half-costa with different boundaries / Nurul Afiqah Abd Malek - Abd Malek, Nurul Afiqah (2020)
Tensioned fabric structure is an outstandingly lightweight and flexible type of roofing structure which are efficient for vast construction applications. This structure has the ability to adopt interesting forms. Minimal surfaces appears to be the most suitable